1990
DOI: 10.7863/jum.1990.9.7.395
|View full text |Cite
|
Sign up to set email alerts
|

Cystic lesions of the prostate gland. A sonographic--pathologic correlation.

Abstract: 277 patients underwent biplane transrectal ultrasonography. Twenty-two patients (7.9%) showed evidence of one or more intraprostatic cystic lesions. Histologic correlation was available with total prostatectomy specimens in six patients and surgical drainage in two patients. Sonographically, 11 patients showed one, 6 patients two, and 5 patients three or more intraprostatic cystic lesions. The size of the lesions ranged from 2 to 30 mm, and the majority of lesions were located within the central portion of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
6

Year Published

1993
1993
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 12 publications
0
14
0
6
Order By: Relevance
“…With the great advance in imaging technology, including CT, MRI and ultrasound (specifically transrectal), it is likely that additional cases will be diagnosed much more frequently. Hamper et al [3] found prostatic cysts in 22 of 277 (7.9%) symptomatic patients, in whom they performed transrectal ultrasonography. Some of the patients had multiple cysts and hence the overall number of cysts in these 22 patients was 53.…”
Section: Discussionmentioning
confidence: 99%
“…With the great advance in imaging technology, including CT, MRI and ultrasound (specifically transrectal), it is likely that additional cases will be diagnosed much more frequently. Hamper et al [3] found prostatic cysts in 22 of 277 (7.9%) symptomatic patients, in whom they performed transrectal ultrasonography. Some of the patients had multiple cysts and hence the overall number of cysts in these 22 patients was 53.…”
Section: Discussionmentioning
confidence: 99%
“…Ils sont souvent volumineux, prennent naissance au niveau du veru montanum et s'étendent dans la partie médiane et postérieure de la prostate entre les canaux éjaculateurs. Ils se différencient de ceux de l'utricule prostatique par l'absence habituelle de communication avec l'urètre [8,9]. De plus, ces kystes ne s'accompagnent pas habituellement d'anomalies des organes génitaux externes.…”
Section: Kystes D'origine Müllérienneunclassified
“…Ils sont très rares et moins fréquents que les kystes müllériens [8]. Ces kystes peuvent être de trois types [10] : kyste unique dans lequel se jettent les deux canaux éjaculateurs ; kyste unilatéral, développé sur un des deux canaux éjaculateurs ; kyste de chaque côté drainant chacun le canal éjaculateur correspondant.…”
Section: Kystes Des Canaux éJaculateursunclassified
See 2 more Smart Citations